Anthropometric Status among 6–9-Year-Old School Children in Rural Areas in Hai Phong City, Vietnam - Hoang, Ngan T.D. (Nutrients, 2018)
A double burden of malnutrition in Vietnamese children has emerged as a key challenge: childhood undernutrition remains a public health concern while childhood overweight/obesity has gradually increased. This study aimed to (1) estimate the prevalence of undernutrition and overnutrition among 6–9-year-old primary school children in rural areas of Vietnam, and (2) identify sociodemographic factors associated with undernutrition and overnutrition in this population. A cross-sectional survey was conducted in October 2016 in 2334 children from eight primary schools in rural areas in Hai Phong City, Vietnam. Anthropometric and demographic data were collected. The prevalence of underweight, stunting, wasting, and anthropometric failure was 8.0%, 5.1%, 5.3%, and 11.9%, respectively. Up to 22.1% of children were affected by overweight/obesity, and 31.0% by abdominal overweight/obesity. Low maternal education was associated with higher odds of underweight and anthropometric failure, whereas overweight/obesity or abdominal overweight/obesity were more likely in boys and children of mothers with a high education level. This study provides evidence for a double burden of diseases among primary school children in rural areas in Hai Phong City. Future interventions for the prevention and control of childhood undernutrition and overweight/obesity should take into account child sex and maternal education level.